Migrant Smuggling: Novel Insights and Implications for Migration Control Policies. Issue 1 (March 2018) - Triandafyllidou, Anna
This article offers a critical review of how migrant smuggling arises out of restrictive migration policies and how it has become increasingly sophisticated and professionalized. Reflecting on the innovative empirical findings presented in the contributions to this volume of The ANNALS, I highlight how migration control has hardened borders, disrupted cross-border flows of goods and people, and transformed local economies. Understanding better the relationship between migration control policies and migrant smuggling and the social and moral nature of the agent-customer transactions has important implications for the policies adopted to address irregular migration and migrant smuggling on both sides of the Atlantic.